Evaluation of Inter and Intraspecific Differences in the Venom Chemical Compositions of Polybia paulista Wasps and Ectatomma brunneum Ants Using FTIR-PAS - Mendonça, Angelica; Bernardi, Rafaella Caroline; Firmino, Ellen Liciane Barbosa; Andrade, Luis Humberto da Cunha; Lima, Sandro Marcio; Fernandes, Wedson Desidério; Antonialli Junior, William Fernando (Sociobiology, 2019)
Wasps can synthesize chemical compounds called venom whose function is to overcome prey and assist in defense of the colonies. Geographic Parameters such as sex, age, the season of the year, and diet determined the composition of the venom location, genetics, environment. However, studies on the compositional variability of venom are still limited due to the difficulty in obtaining samples and the complexity of these substances. This work describes the use of the Fourier Transform Infrared Photoacoustic Spectroscopy (FTIR-PAS) to investigate inter- and intraspecific variability in the venom chemical composition (VCC) of the social wasp Polybia paulista (Von Ihering 1896) and the ant Ectatomma brunneum (Smith 1858). The results reveal significant differences in VCC among the ant and wasp, even for samples obtained from the same environment. The genetic component, therefore, seemed to be the predominant factor determining the compounds present. The findings also showed that exogenous factors, such as diet, could also be responsible for intraspecific differences, especially in wasps. The FTIR-PAS technique proved to be a reliable way of assessing intra- and interspecific differences in social Hymenoptera VCC.